2010
DOI: 10.1016/j.rbmo.2009.11.002
|View full text |Cite
|
Sign up to set email alerts
|

Effect of laser zona thinning on vitrified–warmed embryo transfer at the cleavage stage: a prospective, randomized study

Abstract: The aim of this study was to determine if laser zona thinning could improve the rates of pregnancy and implantation for vitrified-warmed embryo transfer at the cleavage stage. A total of 400 vitrified-warmed embryo transfer cycles were randomly assigned to either the test group or the control group. The zona pellucida of vitrified-warmed embryos in the patients of the control group was untreated, whereas in the test group it was partially thinned by laser just before embryo transfer. In the test group, the cli… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
18
0

Year Published

2010
2010
2021
2021

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 25 publications
(18 citation statements)
references
References 78 publications
(175 reference statements)
0
18
0
Order By: Relevance
“…The duration of embryos in vitrification solution is critically important due to the use of high concentration of CPAs, which is commonly reported within 1 min (Selman et al, 2009;Stanger et al, 2012;Valojerdi et al, 2010;Zhang et al, 2010). However, the equilibration time varied from 5 to 15 min in different reports (Selman et al, 2009;Stanger et al, 2012;Valojerdi et al, 2010;Zhang et al, 2010).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The duration of embryos in vitrification solution is critically important due to the use of high concentration of CPAs, which is commonly reported within 1 min (Selman et al, 2009;Stanger et al, 2012;Valojerdi et al, 2010;Zhang et al, 2010). However, the equilibration time varied from 5 to 15 min in different reports (Selman et al, 2009;Stanger et al, 2012;Valojerdi et al, 2010;Zhang et al, 2010).…”
Section: Discussionmentioning
confidence: 99%
“…For example, the prolongation of exposure time may increase toxicity and influence embryonic developmental potential, whereas shortened exposure may be insufficient for the penetration of CPAs into blastomeres. Most publications emphasized the importance of the duration that embryos should be suspended in the vitrification solution, and most recommend a period of 1 min (Selman et al, 2009;Stanger, Wong, Conceicao, & Yovich, 2012;Valojerdi, Eftekhari-Yazdi, Karimian, Hassani, & Movaghar, 2010;Zhang, Chang, Sone, & Silber, 2010). However, the equilibration times of other studies (Selman et al, 2009;Stanger et al, 2012;Valojerdi et al, 2010;Xie, Zou, Shen, Xiong, & Chen, 2010;Zhang et al, 2010) have ranged from 5 to 15 min.…”
Section: Introductionmentioning
confidence: 99%
“…In our work, this decrease is typical for non hatched blastocysts, while sin gle perforation of hatching or completely hatched blasto cysts had no appreciably affect. Utilization of assisted hatching including laser action for extracorporeal fertilization remains questionable [1,16,17]. In the presented work, we show experimentally that laser action on the zona pellucida at different embryo development stages did not significantly affect ability of embryos to develop until the blastocyst stage.…”
Section: Resultsmentioning
confidence: 72%
“…Besides, very recent studies of a group reported that the procedure does not improve implantation, clinical pregnancy, or live birth rates in women younger than 38 years with embryos having ZP thickness of ≥13 μm [34,35]. Furthermore another very recent study by Valojerdi showed that clinical pregnancy rate was significantly lower with laser assisted zona thinning on vitrified-warmed cleavage stage embryos [36] although it is widely accepted that it gives beneficial results [27].…”
Section: Discussionmentioning
confidence: 99%